Synthesis, Characterization and Chromogenic Properties of 4-Hydroxy-(2-Hydroxybenzylidene) Benzohydrazide - Rassem, Hesham H. A.; Nour, A. H. (IJESRT, 2015)
In this work, hydrazine and hydrazide compounds were subjected to condensation reaction with ketone and different aldehyde derivatives affording the corresponding expected hydrazone, 4-hydroxy-(2-hydroxybenzylidene)benzohydrazide(L1) is synthesized and characterized. The chemical structures were found to be consistent with both analytical and spectroscopic data (CHN, FTIR, UV/Vis, TGA, 1H NMR and 13C NMR). The chromogenic property of the ligand was carried out in differentsolvents including methanol, ethanol, acetone, acetonitrile, dimethylsulphoxide, and tetrahydrofuran.